2008
DOI: 10.1175/2007jcli1847.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tropical Cyclones on the Estimation of Climate Variability in the Tropical Western North Pacific

Abstract: By estimating the differences between the original and tropical cyclone (TC)-removed fields derived from the 40-yr (ECMWF) Re-Analysis (ERA-40) and NCEP–NCAR 40-Year Reanalysis, this study reveals that TCs contribute significantly (exceeding 50% in certain regions) to the seasonal mean and the intraseasonal and interannual variance of the 850-hPa vorticity along the TC tracks in the tropical western North Pacific. Similar effects on the precipitation are also seen, as presented by the examples located in Taiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 19 publications
3
76
1
1
Order By: Relevance
“…It should be mentioned that the TC contribution can be more than 40% along the coastline. These results are also generally consistent with that in Ren et al (2007), Cheng et al (2007), and Hsu et al (2008). It is suggested that changes in TC rainfall should be considered when the rainfall changes in southern and southeastern China are discussed.…”
Section: Changes In Tc Rainfall and Its Contribution To The Summer Prsupporting
confidence: 89%
“…It should be mentioned that the TC contribution can be more than 40% along the coastline. These results are also generally consistent with that in Ren et al (2007), Cheng et al (2007), and Hsu et al (2008). It is suggested that changes in TC rainfall should be considered when the rainfall changes in southern and southeastern China are discussed.…”
Section: Changes In Tc Rainfall and Its Contribution To The Summer Prsupporting
confidence: 89%
“…Hatsushika et al (2006) investigated the TC detection rate in the Japanese 25-years Reanalysis (JRA-25, Onogi et al 2007), and obtained a detection rate of 90%. Hsu et al (2008) extracted TC wind fields from European Centre for Medium-Range Weather Forecasts (ECMWF) 40-years reanalysis project (ERA-40, Uppala et al 2005). They found that TCs contribute significantly (exceeding 50% in certain regions) to the seasonal mean and the intraseasonal and interannual variance of the 850-hPa vorticity along the TC tracks in the tropical western North Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the forcing of the monsoon, a relationship between the interannual variance of the WNP monsoon and the annual maximum discharge in Kratie is found that explains the variation of the scale parameter. It is however acknowledged that other factors play a role in flood generation, such as land use change (Bernard and Koninck, 1997), land management (Haddeland et al, 2006), dam building (Lauri et al, 2012) and local meteorological conditions (Hsu et al, 2008) that may not be related to the larger monsoon circulation. There is however a point in assessing the impacts of a change in the monsoon regime, since it constitutes the dominant factor for floods in the lower Mekong Basin.…”
Section: The 100-year Flood In Kratie Under CCmentioning
confidence: 99%